Coffin man - Doss, James D. (Doss, James D. Charlie Moon mystery., 2011)
Contacted by a frantic Wanda Naranjo to track down her missing sixteen-year-old, eight-months-pregnant daughter, Colorado rancher and part-time tribal investigator Charlie Moon races against time to save the girl.